Characteristics of motorcycle accident victims treated at a leading rehabilitation center in the south of Brazil - Schoeller, Soraia Dornelles; Bonetti, Albertina; Silva, Gelson Aguiar da; Rocha, André; Gelbcke, Francine Lima; Khan, Patricia (Acta Fisiátrica, 2011)
This study outlines the characteristics of motorcycle accident victims treated at a leading rehabilitation center in the south of Brazil. It is a descriptive and quantitative study, which uses results found from research focused on spinal cord injury - SCI. A total of 207 medical records, containing the following information: origin, age, sex, date and cause of injury, were analyzed. The study revealed that victims of motorcycle accidents were most commonly young males (81.09%), 10% of whom were younger than 18 years old. Half of the victims had extremely serious or very serious injuries - SCI, brain injury, or lower limb amputation. The motorcycle accident death rate in in the state of Santa Catarina and in Brazil rose 250% from 2000 to 2009, while the population growth was only 16%. Motorcycle accidents constitute a serious public health problem due to the increase in the number of people injured and the severity of the injuries. Public policies - education, public health and safety, need to be established in order to reverse this trend.